Quantum state engineering with ququarts: application for deterministic QKD protocol - Shurupov, Alexander P.; Straupe, Stanislav S.; Kulik, Sergei P.; Mahmoud Ahmed, Gharib Subhi; Wahiddin, Mohamed Ridza (IOP Publishing, 2009)
We discuss the proof-of-principle demonstration of the extended deterministic Quantum Key Distribution (QKD) protocol based on ququarts. The experimental realization is based on the polarization degrees of freedom of two-mode biphotons, making the process of state preparation, transformation and measurement rather simple. The scheme uses only single nonlinear crystal for biphoton generation and linear optical elements for their following transformation and can be used as a base for further practical applications.